Spectra of some Operations on Graphs - Seidy, Essam EI; Hussein, Salah ElDin; Elkher, Atef Abo (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
In this paper, we consider a finite undirected and connected simple graph G(E, V) with vertex set V(G) and edge set E(G).We introduced a new computes the spectra of some operations on simple graphs [union of disjoint graphs, join of graphs, cartesian product of graphs, strong cartesian product of graphs, direct product of graphs].